Mekanisme Apoptosis Pada Regresi Sel Luteal - Syamsul Hadi, Restu (Lembaga Penelitian Universitas YARSI, 2011)
Corpus luteum is a transient endocrine gland and its presence plays pivotal role in ovulation process, implantation, and luteinization. The regression of corpus luteum or luteolysis is actually needed for next cycle survival and playing a role in providing new follicles.Ã‚Â Luteal regression represents a broad definition of the process of demise of the corpus luteum that is capable of accommodating all new knowledge evolved on the molecular mechanisms activated or inhibited during the process of regression of the corpus luteum. Apoptosis is controlled by a number of regulator genes such as bcl-2 family. The ratio of Bax expression to Bcl-2 is a pivotal factor for a cell to survive or apoptosis. The increasing Bcl-2 expression will lengthen cell life, whereas increasing of Bax expression promotes cell death.